Characters of generic level in wing venation of Dolichopodidae (Diptera) - M.A. Chursina; O.P. Negrobov; O.O. Maslova (Кавказский энтомологический бюллетень, 2012)
The wings of 12 genera of Dolichopodidae (Diptera) have been investigated for revelation of quantitative characters. 15 sections of veins were measured, and 13 coefficients of ratios were obtained. Сoefficients have been verified on reliability using Student's test. Coefficients showed maximally significant differences are suggested for using for diagnosing Dolichopodidae’s genera